Psychopath Analysis in Sweeney Todd Movie - Astri Indriana Octavita; Tiarma Ika Yuliana; M. Ali Ghufron; Rima Novia Ulfa (Candradimuka: Journal of Education, 2023)
Movie is loved by almost people in the world. Many messages can be delivered on a movie. In this case, the writer wants to examine the movie entitled “Sweeney Todd: The Demon Barber of Fleet Street by Tim Burton in 2007. This movie is a drama musical thriller genre because it contains many mysteries that must be paid more attention to understand about the psychological of Todd as the main character. The purpose of this research is to find out the psychopath characteristics of main character. The method that the writer used is qualitative method, after analyzing all the data the writer found that there are 5 characteristics of psychopath, which are: Aggressivity, Criminality, Lying, Violation of the right of others and Behavior that indicates apparent lack of guilty, anxiety and remorse do not have a sense of empathy. The most dominant characteristics of psychopath is Aggressivity.